PEMBERDAYAAN WANITA MELALUI PELATIHAN KETRAMPILAN PADA IBU PKK RT. 02/ RW. 15, KELURAHAN MANGLIAWAN, KECAMATAN PAKIS, KABUPATEN MALANG - Tri Istining Wardani; Esther Hesline Palandi; Dwi Sudjanarti; Diana Eka Poernamawati; Siti Nurbaya; Nilawati Fiernaningsih (Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to enhance entrepreneurial creativity and skills among women members of the PKK RT 02/RW 15, Mangliawan Village, Pakis District, Malang Regency. The training was conducted using a hands-on approach by introducing the decoupage art technique, which involves decorating plain or used items with decorative napkins to increase their aesthetic and economic value. Decoupage art was selected due to its simplicity, affordability, ease of instruction, and potential to transform low-value materials into attractive products. The results show that all participants successfully applied decoupage techniques using two different deco-napkin patterns on two types of media—plastic bags with rough surfaces and flower pots with smooth surfaces—each requiring distinct treatment methods. Overall, the program effectively improved participants’ creativity, knowledge, and practical skills, demonstrating its potential to support women’s empowerment and household-based economic activities.